Impact of cell-free supernatant of lactic acid bacteria on Staphylococcus aureus biofilm and its metabolites - Mao, Yanni; Wang, Yuxia; Luo, Xiaofeng; Chen, Xiaohui; Wang, Guiqin (Frontiers in Veterinary Science, 2023)
Introduction A safe bio-preservative agent, lactic acid bacteria (LAB) can inhibit the growth of pathogenic bacteria and spoilage organisms. Its cell-free supernatant (LAB-CFS), which is rich in bioactive compounds, is what makes LAB antibacterial work. Methods This study focused on the changes in biofilm activity and related metabolic pathways of S. aureus treated with lactic acid bacteria planktonic CFS (LAB-pk-CFS) and biofilm state (LAB-bf-CFS). Results The findings demonstrated that the LAB-CFS treatment considerably slowed Staphylococcus aureus (S. aureus) growth and prevented it from forming biofilms. Additionally, it inhibits the physiological traits of the S. aureus biofilm, including hydrophobicity, motility, eDNA, and PIA associated to the biofilm. The metabolites of S. aureus biofilm treated with LAB-CFS were greater in the LAB-bf-CFS than they were in the LAB-pk-CFS, according to metabolomics studies. Important metabolic pathways such amino acids and carbohydrates metabolism were among the most noticeably altered metabolic pathways. Discussion These findings show that LAB-CFS has a strong potential to combat S. aureus infections.